THE FABRIC OF DIGITAL LIFE: BUILDING AN INTERNET ARCHIVE FOR EMBODIED TECHNOLOGY - Iliadis, Andrew; Pedersen, Isabel (AoIR Selected Papers of Internet Research, 2017)
The Fabric of Digital Life is an Internet archive for storing media related to embodied technologies — things like patents, news releases, instructional videos, and art. The archive allows users to track, catalog, and view artifacts related to human-computer interaction platforms, designs, and ideas, including images, videos, texts, websites, and data sets that document emerging trends. Curated sub-collections are hosted on the archive that relate to a variety of themes, including ethics, surveillance, and vulnerable populations. The underlying motivation is to provide a tool for illustrating the diverse, shared origins of embodied technology platforms, separate from profit-driven inventors and companies. A secondary motivation was to provide a space for thinking about social issues and embodied technologies. The archive allows users to browse keywords (“smart watch” for example) and through a customized metadata scheme users can collect and catalogue embodied technologies and the discourse that surrounds them. Currently, our hope is that researchers who have interests in embodied technologies will begin to use the archive, add to it, and help build the specially curated collections that are inside to highlight the various ways that embodied technologies stand to impact society and culture.